Relações hídricas, trocas gasosas e atividade enzimática de Urochloa ruziziensis inoculada com Azospirillum brasilense, sob déficit hídrico - Bulegon, Lucas Guilherme (2016)
The water deficit causes the plant physiological and biochemical disarray, so is sought ways to reduce these effects and increase the tolerance of plants to water stress. Thus, the present study aimed to evaluate the physiological behavior and biochemical Urochloa ruziziensis inoculated with Azospirillum brasilense via seed and leaf (foliar spray) in conditions induced and controlled water deficit. We used the randomized block design and the treatments, control, inoculation of A. brasilense in seeds, foliar spay application of A. brasilense, combination of seed inoculation and foliar spay application of A. brasilense, segmented into four steps. I - factorial scheme 2x2x13, presence and absence of inoculated seeds, presence and absence of water deficit, and light levels, evaluating gas exchange in moderate drought, severe and rehydration. II - 2x4 factorial scheme, the presence and absence of drought, and the four treatments by assessing daily relative water content, soil moisture and gas exchange. III - was used treatments in drought and irrigated control, being determined, the soluble protein content and the activity of superoxide dismutase, peroxidase (SOD) and catalase, and the contents of chlorophyll a and b, and carotenoid. IV - was the analysis of correlations, track and major components for the plants kept in water restriction and irrigated maintained. The results showed that the use of A. brasilense via seed, makes the culture reach greater photosynthetic activity, less point compensation in severe stress conditions. For water relations, gas exchange and enzyme activity, A. brasilense, inferred positively, especially foliar application, with pronounced effects on stomatal regulation and enzymatic action. By observing the variables linked to maintenance of photosynthesis stood out stomatal conductance (moderate and severe) and SOD (severe). In rehydrating the A. brasilense acted in stomatal and enzymatic regulation, leading to a recovery in order to not harm the plant. It follows that the use of A. brasilense regardless of the form increases the tolerance to water deficit in U. ruziziensis, however foliar application has pronounced effect in relation to the main variables associated with the maintenance of photosynthesis and greater prospect of use